ACUTE SYPHILITIC POSTERIOR PLACOID CHORIORETINITIS: MULTIMODAL IMAGING AND ELECTROPHYSIOLOGIC FINDINGS BEFORE AND AFTER TREATMENT. Issue Volume 15:Issues 6(2021) (November 2021) - Wong, Wendy; Naing, Thet; Bhargava, Mayuri; Chee, Caroline; Lingam, Gopal; Holder, Graham E.
Abstract : Acute syphilitic posterior placoid chorioretinitis is a clinically distinct manifestation of ocular syphilis. The authors describe novel multimodal imaging and electrophysiological findings in the preplacoid stage, as well as changes that occur in the placoid stage, and after treatment. Abstract : Purpose: To describe the clinical course of acute syphilitic posterior placoid chorioretinitis (ASPPC) in the preplacoid stage, placoid stage, and after treatment with penicillin. Method: A retrospective case report of serial multimodal imaging and electrophysiology studies of a patient with ASPPC, with 18 months of follow-up. Results: A 47-year-old man presented with bilateral panuveitis. The patient defaulted follow-up and returned when his vision deteriorated. Tests for neurosyphilis and retroviral disease were positive, and treatment was initiated. The earliest change on serial optical coherence tomography was loss of the signal from the reflective band corresponding to the ellipsoid zone. In the placoid stage, there was nodular thickening of the retinal pigment epithelium. The ellipsoid zone signals reappeared after treatment. Fundus fluorescein angiogram at presentation showed peripapillary vasculitis and disk leakage; indocyanine green angiography revealed multiple hypofluorescent spots in the peripapillary region and posterior pole that was not visible clinically. The angiographic abnormalities resolved after treatment. Electrophysiology demonstrated bilateral maculopathy and reduction of both a- and b-waves from dark-adapted and light-adapted responses at presentation. The b-waves (inner retina) recovered partially with treatment. Conclusion: To the best of our knowledge, this is the first case report of the multimodal imaging and electrophysiology findings in a patient with acute syphilitic posterior placoid chorioretinitis, before the development of the classic placoid lesion. Improvement of structural and functional pathology after systemic treatment is demonstrated.